Pengaruh ideologi dan religiusitas terhadap Altruisme guru di yayasan darul Athfal ranjok - Kinayatul Khofia; Sarifudin Serip (GLOBAL SCIENTS PUBLISHER, 2026)
This research is driven by the phenomenon of diverse teacher attitudes at Yayasan Darul Athfal Ranjok, where indications of low average altruistic behavior were found, characterized by a lack of initiative in activities outside core teaching duties. This study aims to analyze and empirically test the influence of Ideology (X1) and Religiosity (X2) variables on the level of Altruism (Y) among teachers at the foundation. The type of research used is causal associative research with a quantitative approach. The population in this study consists of all 34-teaching staff at Yayasan Darul Athfal Ranjok. Given the relatively small population size, the sampling technique employed is the census method or saturated sampling. Primary data were obtained through the distribution of questionnaires, structured interviews, and documentation studies. Data analysis was performed using multiple linear regression analysis assisted by SPSS software. The results of the study indicate the following findings: (1) Ideology has a positive and significant influence on teacher altruism with a regression coefficient of 0.430 and a significance value of 0.004 (< 0.05). (2) Religiosity has a positive and significant influence on teacher altruism with a regression coefficient of 0.564 and a significance value of 0.003 (< 0.05). (3) Simultaneously, Ideology and Religiosity significantly influence altruistic behavior with an F-value of 6.923 and a significance of 0.003 (< 0.05). The Coefficient of Determination (R2) of 0.611 indicates that the Ideology and Religiosity variables are able to explain the variation in altruistic behavior by 61.1%, while the remaining 38.9% is influenced by other factors outside this research model.